Rancang Bangun Sistem Pengangkat Pada Forklift Mini Dengan Kapasitas Angkat Maksimum 150 Kg - Oktavian, Halvian; Malik, Yulianti; Darmadi, Herry; Kurnia, Dian (CV. IRA PUBLISHING, 2024)
Forklifts are one solution to this problem. Material to be lifted This mini forklift is limited to a maximum weight of 150 kg. Therefore, equipment The lifter is designed in such a way that it is able to withstand the maximum load at the time operated. In the lifting system on this mini forklift, a 12 volt battery is used provides supply to the linear actuator where the linear actuator will move or control system mechanism. In this study, a tool was used to control outward movement The entry actuator is a push button. Based on the results that have been obtained starting from planning to testing, obtained stable forklift results during lifting and carries loads with a maximum lifting capacity of 150 kg and a lifting height of 140 cm.